Industrial and process furnaces principles, design and operation - Mullinger, Peter; Jenkins, Barrie (Butterworth-Heinemann, 2022)
Industrial and Process Furnaces: Principles, Design and Operation, Third Edition?continues to provide comprehensive coverage on all aspects of furnace operation and design, including topics essential for process engineers and operators to better understand furnaces. New to this edition are sections on production, handling and utilization of alternative fuels such as biomass, hydrogen and various wastes, modeling of the process, combustion and heat transfer, their benefits, advantages and limitations, mitigation and removal of CO2 , the role of solar and other renewable energy, recent research, and the practical approach of the Whyalla steelworks for harnessing solar energy for sustainable steelmaking, hydrogen and as a "clean fuel". The book also includes a discussion on the limitations of hydrogen supply owing to fresh water supply constraints, the difficulty of storing and transporting hydrogen, and the current sociopolitical impetus of CO2.